2021
DOI: 10.1007/s00464-021-08393-2
|View full text |Cite
|
Sign up to set email alerts
|

A new minimally invasive technique for the repair of diastasis recti: a pilot study

Abstract: Background Diastasis recti is an abdominal wall defect that occurs frequently in women during pregnancy. Patients with diastasis can experience lower back pain, uro-gynecological symptoms, and discomfort at the level of the defect. Diastasis recti is diagnosed when the inter-rectus distance is > 2 cm. Several techniques, including both minimally invasive and open access surgical treatment, are available. Abdominoplasty with plication of the anterior rectus sheath is the most commonly used, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…The review of current literature identified 264 studies, of which 10 studies met the inclusion criteria [19][20][21][22][23][24][25][26][27][28], Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review of current literature identified 264 studies, of which 10 studies met the inclusion criteria [19][20][21][22][23][24][25][26][27][28], Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…1. The reports fulfilling these criteria included two randomized controlled studies (RCTs) [21,28] and eight prospective cohort studies [19,20,[22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations